Systematic Literature Review: Communication Transformation in The Digital Immigrant Generation in The Use of Social Media and Changes in Social Interaction Patterns - Sembiring, Putri Sosanti; Dwianita, Dwianita; Maharani, Blangi Intan (Program Pascasarjana UIN Sumatera Utara, 2025)
The transformation of digital technology has brought significant changes in the way humans communicate. The digital immigrant generation, individuals who were born before the digital era but adapted to technology, experience challenges and changes in their daily communication patterns. This article is a literature review that examines how communication transformation in the digital immigrant generation in the use of social media and its impact on social interaction patterns. Digital immigrants face challenges in digital literacy and information security, but social media allows them to stay connected with their families and form new communities. By reviewing previous studies, this article describes the adaptation process of digital immigrants to social media, the barriers they face, and how social media opens up spaces of social inclusion for digital immigrants, allowing them to form new communities, communicate across generations, and reduce loneliness.